CT evaluation of flank pain and suspected urolithiasis - Alshamakhi, A.; Barclay, L.; Halkett, Georgia; Kukade, G.; Mundhada, D.; Uppoor, R.; Gawai, P. (American Society of Radiologic Technologists, 2009)
Background Acute renal colic is the most common clinical indication among patients seen in emergency departments. Studies have shown that 2% to 3% of people will experience an episode of acute renal colic during their lifetime. Objective The objective of this study was to create and pilot test a single efficient medical imaging examination that can assess the entire urinary system and the surrounding organs’ parenchyma for flank pain, suspected urolithiasis or both. Methods Participants were scanned using a single-slice computed tomography unit (Secura, Philips Healthcare, Boston, Massachusetts). A total of 57 patients who were suffering from flank pain, suspected of having urinary stones or both participated in the study. Results and Conclusion The results indicate that nonenhanced CT scans facilitate more accurate assessments in the diagnosis of acute flank pain and urolithiasis than other medical imaging evaluations such as KUB radiographs (kidneys, ureters and bladder ), intravenous urography and ultrasonography. In addition, the current study showed that patients did not experience any complications following the use of water as an oral contrast media.